2018
DOI: 10.4269/ajtmh.17-0621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Plasmodium falciparum Glutamate-Rich Protein R2 Region Before and Twelve Years after Introduction of Artemisinin Combination Therapies among Febrile Children in Nigeria

Abstract: The genetic diversity of glutamate-rich protein () R2 region in isolates collected before and 12 years after the introduction of artemisinin combination treatment of malaria in Osogbo, Osun State, Nigeria, was compared in this study. Blood samples were collected on filter paper in 2004 and 2015 from febrile children from ages 1-12 years. The R2 region of the gene was genotyped using nested polymerase chain reaction and by nucleotide sequencing. In all, 12 alleles were observed in a total of 199 samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…By CE, fragments differing as little as 3 base pairs in size can be distinguished. In contrast, when binning using gels, resolution might be as low as 50 base pairs [ 35 ]. Previous studies comparing the two methods directly showed that CE yields higher multiplicity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…By CE, fragments differing as little as 3 base pairs in size can be distinguished. In contrast, when binning using gels, resolution might be as low as 50 base pairs [ 35 ]. Previous studies comparing the two methods directly showed that CE yields higher multiplicity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to artemisinin is well documented in Vietnam, Western Cambodia and Thai-Myanmar borders [ 7 ]. Since a significant proportion of the Vietnamese population lives in malaria endemic areas, where resistant phenotypes have been reported, studies to decipher the genetic diversity and multiplicity of infections (MOI) of P. falciparum are essential to understand the intensity of transmission, epidemiological patterns and virulence of the parasites and, in particular, to evaluate measures aimed at malaria control [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first study in Assam, Northeast India reported ten different types of glurp alleles based on their base pair sizes [ 61 ]. Similarly, in Nigeria, 12 alleles of glurp were reported before and after ACT implementation [ 62 ]. Later, nine allele types of glurp were reported from Northeast Indian states of Arunachal Pradesh [ 40 ] and Tripura [ 51 ].…”
Section: Discussionmentioning
confidence: 99%